Modelling Definition in Mechanical Engineering Texts Viewed from SFL - Khorina, Mulyati (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2023)
Introductory textbooks of undergraduate students contain commonly accommodate numerous technical terms which are commonly in form of abstract nouns. The technical terms naturally represent the knowledge of the discipline which serve to build the knowledge of the field. Unfortunately, the technical terms tend to use abstract words which require definition to understand them. Hence, understanding the construction of a definition will help the learners of the field understand the texts. Therefore, the purpose of this study was to investigate the construction of definition appearing in technical terms appearing in disciplinary texts, like mechanical engineering textbooks. The qualitative data were collected from introductory textbooks of mechanical engineering. The results of analysis using Systemic Functional Linguistics (SFL) reveal several findings. First, definition is realized by clause complex consisting of main clause and subordinate clause. Consequently, the clause has hypotactic relation and semantic one. The main clause is realized by intensive clause with relational process realized by some lexical verbs. Whereas subordinate clause is realized by non-finite or finite clause of possessive or circumstantial clause. The subordinate clause semantically serves as elaboration of the Thing in the main clause. The elaboration can be formed as function/properties/duration/condition/results which make the Thing in the main clause definite. Based on these findings, definition can be formulated as intensive clause (main clause) + possessive/circumstantial clause of non-finite/finite clause (subordinate clause). The findings also have implication on ESP or EAP learning which can help learners in academic reading and writing.